2021
DOI: 10.1002/ijc.33545
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomatoid hepatocellular carcinoma is distinct from ordinary hepatocellular carcinoma: Clinicopathologic, transcriptomic and immunologic analyses

Abstract: Sarcomatoid hepatocellular carcinoma (SHCC), which was a rare histological subtype of hepatocellular carcinoma (HCC), is currently subclassified as poorly differentiated HCC because of insufficient evidence to define SHCC as a subtype of HCC. We aimed to assess the feasibility of classifying SHCC as a histological subtype of HCC by comprehensively identifying novel and distinct characteristics of SHCC compared to ordinary HCC (OHCC). Fifteen SHCCs (1.4%) defined as HCC with at least a 10% sarcomatous component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 46 publications
4
39
0
Order By: Relevance
“…Kodama T et al identified cancer‐related genes such as MET , GAB1 , and HECT that may drive epithelial‐mesenchymal transition in HCC 17 . Morisue R et al detected the transcriptome in two sarcomatoid HCCs and five non‐sarcomatoid HCC and found upregulation of genes that associated with epithelial‐to‐mesenchymal transition and inflammatory responses in sarcomatoid HCC 18 . In our study, we found distinct genetic patterns between sarcomatoid HCC and non‐sarcomatoid HCC.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Kodama T et al identified cancer‐related genes such as MET , GAB1 , and HECT that may drive epithelial‐mesenchymal transition in HCC 17 . Morisue R et al detected the transcriptome in two sarcomatoid HCCs and five non‐sarcomatoid HCC and found upregulation of genes that associated with epithelial‐to‐mesenchymal transition and inflammatory responses in sarcomatoid HCC 18 . In our study, we found distinct genetic patterns between sarcomatoid HCC and non‐sarcomatoid HCC.…”
Section: Discussionsupporting
confidence: 60%
“…17 Morisue R et al detected the transcriptome in two sarcomatoid HCCs and five non-sarcomatoid HCC and found upregulation of genes that associated with epithelial-to-mesenchymal transition and inflammatory responses in sarcomatoid HCC. 18 In our study, we found distinct genetic patterns between sarcomatoid HCC and non-sarcomatoid HCC. The major finding was that sarcomatoid HCC had a high rate of rearrangement and homozygous deletion in CDKN2A gene, which leads to a loss of gene function.…”
Section: Discussionsupporting
confidence: 48%
“…Recently, features of immune infiltration were revealed for the first time, which contained pathological tissues from 31 cases, that PD-L1 expression of SHC was significantly higher than that of HCC, which also associated with poor prognosis in DFS (HR= 5.036, 95% CI 1.382–18.354) and OS (HR=5.696, 95% CI 1.473–22.081). 47 , 50 It suggests that individualized analysis of immune check point and immunotherapy might be beneficial in PLSC patients, but adverse events still have to be carefully monitored.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Studies consistently show that SHCC is associated with worse outcomes and is considered an independent unfavorable prognostic indicator. 11 , 18 …”
Section: Discussionmentioning
confidence: 99%